Methods and applications of statistics in clinical trials - Balakrishnan, N. 1956- (Hoboken, New Jersey John Wiley & Sons Inc., 2014)
This comprehensive book features both new and established material on the key statistical principles and concepts for designing modern-day clinical trials, such as hazard ratio, flexible designs, confounding, covariates, missing data, and longitudinal data. It discusses the various kinds of trials that can be found in today's clinical setting including open-labeled trials, multicentered trials, and superiority trials. It also explores such ongoing, cutting-edge trials as early cancer & heart disease, mother to child human immunodeficiency virus transmission, women's health initiative dietary, and AIDS.
Volume 1. Concepts, principles, trials, and design -- volume 2. Planning, analysis, and inferential methods.
Includes bibliographical references and index.
Keywords: Clinical trials -- Statistical methods; Clinical Trials as Topic; Statistics as Topic